Performance evolution of TLD-700H/600H dosimetry system at extended issue periods. (January 2018) - Romanyukha, Alexander; Grypp, Matthew D.; Trompier, François; Thompson, Alan K.; Minniti, Ronaldo; Debroas, Jacques; Williams, Anthony S.
Abstract: Results of a comprehensive study of the TLD-700H/600H (Harshaw 8840/8841) dosimetry system performance for an extended issue period are presented and discussed. The results provide a technical justification to use the current dosimetry system issues periods up to almost 600 days, far beyond the current 95-day issue period used at the Naval Dosimetry Center (NDC). Extending (or reducing) the issue period has a statistically significant effect on the uncertainty of the dose equivalent values measured within the dosimetry system. In order to accommodate the use of various issue periods for the dosimetry system, the lower limit of detection (LLD) linear model is proposed. A possible limitation of this model (dose fading) is discussed. The factors responsible for both time independent and dependent LLD components are identified. The thermoluminescent residual signal and dosimetry system calibration are responsible for the time-independent LLD component; whereas the factors for time-dependent LLD component are dose fading, radiation background and its standard deviation. Simple formulae for photon and neutron LLDs at variable dosimeter issue periods are proposed. As a result of the experimental study conducted, multiple LLD components were numerically evaluated for the four-element TLD-700H/600H dosimetry system at different issue periods. Implementation of these formulae in the Dose Program may provide a more accurate LLD estimation for each reported dose equivalent at any technically justified dosimeter issue period. Highlights: Results of a comprehensive study of the TLD-700H/600H dosimetry system performance for an extended issue period are presented and discussed. The obtained results provide a technical justification to use the current dosimetry system at up to almost 600 days issue period. The lower limit of detection (LLD) linear model is proposed. The proposed LLD formulae are capable to provide an accurate LLD for each reported dose equivalent at any dosimeter issue period.